Characterization of muscle oxygenation response to vascular occlusion: implications for remote ischaemic preconditioning and physical Performance. (2nd March 2016) - Cunniffe, B.; Sharma, V.; Cardinale, M.; Yellon, D.
Summary: Remote ischaemic preconditioning is a non‐invasive intervention with potential to protect a number of organs against ischaemia–reperfusion injury and possibly improve athletic performance. Little mechanistic evidence exists to support either limb choice or cuff inflation pressure that is most effective. This preliminary study aimed to establish the dose–response effect of different occlusion pressures on skeletal muscle oxygenation and blood flow in healthy males ( n  =   6). In a randomized controlled crossover study, cuff inflation pressures (140, 160 and 180 mmHg) were used to induce limb ischaemia (× 3 cycles of 5‐min) in upper (UL) and lower (LL) limbs on three separate occasions. Muscle oxygenation and blood flow properties of UL ( flexor carpi ulnaris ) and LL ( vastus lateralis ) were assessed using near infrared spectroscopy. Higher deoxyhaemoglobin (ΔHHb) values were consistently observed in UL (versus LL; P <0·05), no difference between pressures. Occlusion at 140 mm Hg failed to elicit decreases in tissue oxyhaemoglobin (ΔHbO2 ) from resting baseline (UL and LL), with significant HbO2 decreases only observed at 180 mmHg in LL ( P <0·05). Increases in ΔHbO2 and muscle oxygenation index (Hbdiff ) above baseline were observed with cuff deflation, lasting up to 15 min into recovery in LL irrespective of occlusion pressure ( P <0·05). Muscle oxygenation properties are influenced by choice of limb occluded and findings show that tissue ischaemia can be induced at much lower absolute pressures than traditionally used in RIPC studies. Blood flow and muscle oxygenation may be enhanced for at least 15 min following the last occlusion.